Disparitas Pemidanaan dalam Perkara Narkotika: Analisis Proporsionalitas Putusan Nomor 105/Pid.Sus/2023/PN Plj - Ainul Badri; Lailatul Qodriyanti; Muhammad Ikhwan (IAIN Langsa, 2026)
This study aims to analyze the factors contributing to sentencing disparity, judicial considerations, and the conformity of sentencing with the principle of proportionality in Decision Number 105/Pid.Sus/2023/PN Plj. This study employs a normative juridical legal research method using statutory, conceptual, and case approaches through an analysis of the court decision and relevant legal literature. The findings indicate that sentencing disparity is influenced by the broad discretion afforded to judges, the lack of optimal standardized sentencing parameters, differences in the degree of offenders’ involvement, and a predominantly repressive orientation in addressing narcotics offenses. The panel of judges sentenced ODS to five years and six months of imprisonment and NP to five years of imprisonment, with each receiving a fine of IDR 1,000,000,000, subsidiary to six months of imprisonment. This difference indicates an attempt to apply individualized sentencing; however, the sentencing gap does not fully reflect the differences in the roles and levels of culpability of the defendants. This study contributes to strengthening sentencing policy by emphasizing the need for more objective, measurable, and proportional sentencing guidelines to minimize disparities without undermining judicial independence.